2022
DOI: 10.14202/vetworld.2022.1523-1529
|View full text |Cite
|
Sign up to set email alerts
|

Effects of common litter types and their physicochemical properties on the welfare of broilers

Abstract: Background and Aim: In broiler production, the poor quality litter not only may lead to a deterioration of the welfare status but also negatively affect carcass quality, overall health and growth performance, which may result in economic losses. The effects of litter types on the welfare of broilers are known but the effects of their characteristics have been little studied. This study aimed to evaluate correlations between welfare parameters of broilers and physicochemical characteristics of five common litte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
0
4
0
2
Order By: Relevance
“…Lower FPD incidence in broilers kept on pellets was also reported by Kheravii et al 16 . The other research examined standard-quality straw, low-quality straw, wood shavings, sawdust, and crop residues 44 . It was found that the bedding material significantly affected the footpad condition in broiler chickens.…”
Section: Discussionmentioning
confidence: 99%
“…Lower FPD incidence in broilers kept on pellets was also reported by Kheravii et al 16 . The other research examined standard-quality straw, low-quality straw, wood shavings, sawdust, and crop residues 44 . It was found that the bedding material significantly affected the footpad condition in broiler chickens.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, broilers raised on straw had a 20% higher prevalence of FPD than those raised on wood shavings, which is consistent with the findings of Skrbic et al [23] who reported a higher incidence of FPD in broilers raised on straw. Boussaada et al [22] and Sirri et al [24] also found that litter type significantly affected contact dermatitis development, with broiler flocks raised on wood shavings showing less dermatitis than those raised on straw.…”
Section: Characterization Of the Broiler Farms Studiedmentioning
confidence: 97%
“…Litter types is one of the most important factors affecting incidence and prevalence of FPD in broiler chickens. However, the development of FPD could be due to a prolonged contact with poor bedding materials [21,22].…”
Section: Characterization Of the Broiler Farms Studiedmentioning
confidence: 99%
“…As with contact dermatitis of the pads and hocks reviewed earlier, factors such as the quality of the litter or bedding material, the amount of moisture and humidity in the environment, and the presence of feces or urine can all contribute to soiling or contamination of feathers [27,29]. Boussaada et al [71] revealed that the use of sawdust or wood shavings as bedding materials resulted in improved feather cleanliness compared with straw or crop residues, and there was a positive correlation between the feather cleanliness and the litter score integrated with moisture, water holding capacity, pH, and ammonia of the bedding (r = 0.39, p < 0.05). To maintain good feather cleanliness, it is important to ensure that the litter or bedding is clean, dry, and changed regularly, and that the environment is well-ventilated and free from excess moisture [50].…”
Section: Litter Qualitymentioning
confidence: 99%